PENGEMBANGAN MEDIA FUN THINKERS BOOK PADA TEMA 1 MATA PELAJARAN PKN MENGGUNAKAN PEMBELAJARAN INTERAKTIF DAN MENYENANGKAN UNTUK SISWA KELAS 3 SD NEGERI 3 LENDANG NANGKA - Yani, Lusi (Buletin Ilmiah Pendidikan, 2023)
This study aims to develop Fun Thinker Book learning media and determine the level of feasibility of the media, in terms of validation experts and the level of feasibility in terms of student responses to teaching media developed in theme one subtheme 1 Civics learning about Understanding the meaning of images on the national emblem garuda pancasila in grade 3 SD Negeri 3 Lendang Nangka. This type of research is research and development (R & D), which aims to produce products with the research and development model used in this study, the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The use of the research model aims to produce viable learning media products. The data collection instruments used are observation, interviews, and validation sheets, questionnaire sheets for student responses regarding learning media. The fun Thinker book learning media product was developed as a framed book with nine tiles. The book contains six learning exercises that can be understood using frames and tiles. The validation results obtained from material experts were 95.38%, media experts 90.90%, and student response questionnaire results 92.22%. The validation results of material experts media experts show that the fun Thinker book media is very valid for learning. The results of the questionnaire of student responses regarding learning media in field trials showed that the level of media interest reviewed by student responses about the fun thinker book media was very valid.